Successful outcome of renal transplantation in a child with HIV-associated nephropathy. Issue 11 (14th August 2014) - Shroff, Rukshana C; McCulloch, Mignon; Novelli, Vas; Shingadia, Delane; Bradley, Suzanne; Clapson, Margaret; Mamode, Nizam; Marks, Stephen D
Abstract : Classical HIV-associated nephropathy (HIVAN) was first described before the advent of highly active antiretroviral therapy in late stages of HIV disease with high viral load and low CD4 cell count. Renal transplantation has been successful in a large series of carefully selected HIV-infected adults, with patient and renal allograft survival approaching those of non-HIV-infected patients. We report the successful outcome of living related renal transplantation in a vertically transmitted HIV-infected 8-year-old girl with end-stage kidney disease on haemodialysis due to HIVAN. The pretransplant preparations and post-transplant care, with particular emphasis on immunosuppression and avoidance of opportunistic infections, are discussed.